1999
DOI: 10.1007/s002109900050
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of mdr1b-type P-glycoprotein to okadaic acid resistance in rat pituitary GH 3 cells

Abstract: Okadaic acid as well as other, structurally different, inhibitors of serine/threonine phosphatases 1 and 2A induce apoptosis in pituitary GH3 cells. Incubation with stepwise raised concentrations of okadaic acid resulted in the isolation of cells that were increasingly less sensitive to the cytotoxic effect of this agent. After about 18 months cells were selected that survived at 300 nM okadaic acid, which is about 30 times the initially lethal concentration. This study revealed that a major pharmacokinetic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Together, these findings support our results and provide evidence that P-gp exerts a negligible effect in the distribution of [ 3 H]cortisol and [ 3 H]corticosterone at the BCSFB. Because P-gp has also been detected in rat and human pituitary cells (36, 37), it can be concluded that although P-gp is present and functioning in the murine choroid plexus and in the pituitary gland, P-gp does not significantly affect the accumulation of [ 3 H]cortisol or [ 3 H]corticosterone in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings support our results and provide evidence that P-gp exerts a negligible effect in the distribution of [ 3 H]cortisol and [ 3 H]corticosterone at the BCSFB. Because P-gp has also been detected in rat and human pituitary cells (36, 37), it can be concluded that although P-gp is present and functioning in the murine choroid plexus and in the pituitary gland, P-gp does not significantly affect the accumulation of [ 3 H]cortisol or [ 3 H]corticosterone in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…P-glycoprotein is a good candidate to expel okadaic acid out of the cells in bivalve mollusks because it transports a wide variety of structurally unrelated hydrophobic amphipathic compounds (such as okadaic acid) across membranes [25]. Furthermore, both functional and biochemical data support the proposal that okadaic acid is a substrate of the P-gp-mediated efflux activity in rat pituitary GH3 cells [6]. In addition, Ehlers et al [26] have shown that OA is a substrate of human P-gp and that P-gp is involved in the elimination of OA from cells using two different transwell models: (i) caco-2 cell monolayer endogenously expressing human P-gp, simulating the intestinal barrier and (ii) MDCK-II cell monolayer stably over-expressing P-gp.…”
Section: Introductionmentioning
confidence: 77%
“…Thus, OA blocks the dephosphorylation of proteins that are substrates of protein kinases, affecting many basic processes, such as the regulation of gene expression, cell-cycle control, cell adhesion, apoptosis, or cytoskeleton dynamics [ 4 , 5 ]. It has also been demonstrated that low concentrations of OA have cytotoxic and mutagenic effects on different cell lines and on different bivalve tissues [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%